Prioritization of Negative Carbon Strategies in the Cargo Industry with the SWARA/WASPAS Method - Onur Derse; Emel Yontar (Journal of Advanced Research in Natural and Applied Sciences)
The ever-increasing consumption of fossil fuels with the increasing population in the world has brought along the obligation of countries to take some precautions. Determining the measures to be taken to prevent carbon emissions, turning these measures into a strategy and implementing them has become one of the important issues that concern almost every field. Reducing, neutralizing and turning negative carbon emissions significantly reduces the side effects of climate change. In this study, it is aimed to develop strategies within the scope of carbon negative by considering the cargo sector, which is one of the important fields of activity of the transportation sector, where the carbon emission rate is high. SWARA and WASPAS methods, which are among the Multi-Criteria Decision Making methods, are used in the evaluation phase of the strategies determined through the Delphi technique and literature review. Strategies are asked to be prioritized for the implementation of 16 determined strategies within the cargo sector, and “Using electric vehicles” ranked first in both methods. “Use of carbon capture, exploitation and storage technologies”, “Balancing greenhouse gas emissions”, “Existence of carbon tax to reduce carbon emissions” strategies have also been identified as other top priority strategies. It is thought that the strategies listed as a result of the study can help reduce our carbon footprint and help reach negative carbon by reducing CO2 levels in the atmosphere.